Diversi Sebagai Bentuk Penyelesaian Tindak Pidana Penganiayaan yang dilakukan oleh Anak Melalui Pendekatan Keadilan Restoratif - Mushesi, Fitri Silvia; Setiyono, Setiyono (Postgraduate University of Merdeka Malang, 2023)
Criminal acts of abuse can be diverted based on the principles of restorative justice on the grounds of protecting the rights of children as victims and the rights of children as perpetrators. Resolution using the principles of restorative justice in the justice system is only carried out at the investigation stage. The formulation of the problem taken in this research is, first, how is diversion implemented as a form of resolving cases of criminal acts of abuse committed by children through a restorative justice approach in the jurisdiction of the Banjarmasin Police, second, what are the obstacles for investigators in implementing diversion as a form of resolving cases of criminal abuse committed? By children through a restorative justice approach. The research method used is empirical legal research. The results of the research show that the application of restorative justice in criminal acts of abuse committed by children at the Banjarmasin Police has carried out restorative justice efforts in accordance with applicable regulations and procedures that have been in force, although the results of the resolution of cases of criminal acts of abuse committed by children are not yet complete. Successful, and the success rate only reached 8.33%, and the obstacles faced in resolving cases of criminal acts of abuse committed by children are, a) In terms of Human Resources, Facilities and Infrastructure.